Modeling martensitic phase transformation in dual phase steels based on a sharp interface theory - Ruck, Johannes (Schriftenreihe Kontinuumsmechanik im Maschinenbau, 2021)
Martensite forms under rapid cooling of austenitic grains accompanied by a change of the crystal lattice. Large deformations are induced which lead to plastic dislocations. In this work a transformation model based on the sharp interface theory, set in a finite strain context is developed. Crystal plasticity effects, the kinetic of the singular surface as well as a simple model of the inheritance from austenite dislocations into martensite are accounted for.